Effects of Psychological Benefits of Greenness on Airlines’ Customer Experiential Satisfaction, Service Fairness, Alternative Attractiveness, and Switching Intention - Chan, Suk Ha Grace; Zhang, Xiaocheng Vicky; Wang, Yifan Betty; Li, Zhaofeng Mason (Frontiers in Psychology, 2022)
In the context of climate change, this study uncovers the role of green airlines’ social responsibility in conjunction with consumers’ switching behavior while considering the effects of latent variables, including green psychology, airline corporate image, green experimental behavior, green service fairness, and green alternative attractiveness. The predicted relationship based on partial least squares structural equation modeling of a convenience sample of 615 valid data sets collected from individuals who use green airline services in China. Findings show that the psychological benefit of greenness, only warm glow, is the main driver of airline corporate image. Furthermore, airline corporate image, green service fairness, and green alternative attractiveness support passengers’ green experiential satisfaction. Evidence demonstrates that green experiential satisfaction and green alternative attractiveness have significantly positive effects on switching intention. However, green service fairness has no significant effect on green switching intention. This study contributes to the literature by understanding airline customers’ perception of the complex relationship in the green constructs. This finding can help marketers facilitate and develop their external communication and craft their image to retain their existing or potential customers.